2013
DOI: 10.1016/j.adolescence.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of loneliness during childhood and adolescence: Predictors and health outcomes

Abstract: The present study employed latent growth mixture modeling to discern distinct trajectories of loneliness using data collected at 2‐year intervals from age 7–17 years (N = 586) and examine whether measures taken at age 5 years were good predictors of group membership. Four loneliness trajectory classes were identified: (1) low stable (37% of the sample), (2) moderate decliners (23%), (3) moderate increasers (18%), and (4) relatively high stable (22%). Predictors at age 5 years for the high stable trajectory wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
254
8
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(288 citation statements)
references
References 59 publications
21
254
8
5
Order By: Relevance
“…Much of the literature has examined the extent to which risk factors such as negative reactivity, low levels of social engagement, negative cognitive style, low self-esteem, and low trust beliefs in others predispose adolescents to experience increasing level of loneliness (e.g., Qualter et al, 2013). However, moderators of the influence of loneliness on depression have not been identified or studied.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 99%
“…Much of the literature has examined the extent to which risk factors such as negative reactivity, low levels of social engagement, negative cognitive style, low self-esteem, and low trust beliefs in others predispose adolescents to experience increasing level of loneliness (e.g., Qualter et al, 2013). However, moderators of the influence of loneliness on depression have not been identified or studied.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 99%
“…Qualter et al [32] found that persistently high levels of loneliness as well as moderately increasing levels of loneliness between ages 5 and 17 were positively associated not only with depressive symptoms but also with frequency of doctor visits, and negatively associated with self-rated health at age 17. In a study of 11-15 year olds in nine European countries, affiliation deficits, as indicated by higher levels of loneliness, were associated with worse physical health and well-being; in addition, low well-being was associated with lower levels of social integration [51], suggesting a negative cycle of diminishing social connectedness and well-being.…”
Section: (C) Adolescence (13-17 Years)mentioning
confidence: 99%
“…poorer general health [27]; more somatic symptoms [28] ! poorer general health [32,51]; see also [28,34] ! poorer general health [33,34] !…”
Section: Loneliness and Its Health Effects Across The Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…This subgroup consists of individuals who report persistent loneliness over many years and report feeling socially or emotionally distant from others. In several multiwave longitudinal studies, researchers investigating developmental trajectories of loneliness from childhood through early adulthood have indicated that between 3% and 22% of people experience prolonged loneliness (Benner, 2011;Harris, Qualter, & Robinson, 2013;JobeShields, Cohen, & Parra, 2011;Ladd & Ettekal, 2013;Qualter, Brown, et al, 2013;Schinka, Van Dulmen, Mata, Bossarte, & Swahn, 2013;Vanhalst, Rassart, et al, 2013). Further, despite a dearth of studies in which researchers investigated prolonged loneliness in middle adulthood, stability and change in loneliness among older adults have been investigated by researchers using retrospective and longitudinal designs.…”
Section: Sources Of Transient and Prolonged Feelings Of Loneliness Acmentioning
confidence: 99%